Effective admission and congestion control for interconnection networks of cluster computing systems. (26th May 2009) - Yan, Shihang; Min, Geyong; Awan, Irfan
Admission and congestion control mechanisms are integral parts of the design and provision of Quality of Service (QoS) in interconnection networks. This study investigates the admission and congestion control mechanisms for InfiniBand networks in cluster-based computing systems. This paper presents an improved Link-by-Link (LL) admission control algorithm. In addition we propose an effective source response function which adopts the rate control to reduce congestion of multiple-class traffic in InfiniBand networks. Performance results obtained from simulation experiments and the comparison to existing schemes have demonstrated that the proposed admission control algorithm and the new resource response function are quite effective and suitable for InfiniBand networks.